A review of the technical-economic analysis of personal electric vehicle integration in the MENA region - Karmich, Saida; El Malki, Mohamed; Maaouane, Mohamed; Ziani, El Mostafa; Bouchnaif, Jamal; Arabi, Mourad (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
The technical-economic viability of hybrid renewable energy systems that include personal electric vehicles (EVs) in the Middle East and North Africa (MENA) area is assessed in this study. We examined several microgrid configurations using HOMER Grid software, focusing on the effects of electricity prices and subsidy policies. The results show how the hybrid combination of photovoltaic with the grid provided the most significant configuration across the MENA region according to the sensitivity studies that indicate considerable potential for wider application. Eliminating subsidies and modifying power rates are two important tactics for promoting the use of hybrid renewable energy systems. For policymakers and investors in the MENA area, these studies provide practical insights.